Something borrowed, someone dead [large type] : an Agatha Raisin mystery - Beaton, M. C. (Beaton, M. C. Agatha Raisin mystery., 2013)
Hired by the Parish councilor of a small community in the Cotswold Hills to investigate the murder of a jolly widow, Agatha Raisin learns about the victim's penchant for keeping borrowed items in a case that is complicated by village secrets and a killer who would make Agatha a next target.